Investigation of X-ray computed tomography as a tool for non-destructive evaluation of components produced by 3D printing - Ho, Vanessa Kah Hui (2016)
Additive manufacturing is seen to the next big thing as it has a major competitive advantage over the rest of other traditional manufacturing technology due to the flexibility in the design of the product and the potential cost savings due to the reduction in the amount of material used to produce a part. Hence, it is of upmost importance to ensure that the 3D printed part satisfy certain criteria such as porosity level. Thus, this project proposes methods to analyse the porosity of a 3D printed stainless steel specimen.